2016
DOI: 10.1016/j.yexcr.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Ectodomain cleavage of FLT1 regulates receptor activation and function and is not required for its downstream intracellular cleavage

Abstract: Flt1 is a cell surface VEGF receptor which is cleaved to release an N-terminal ectodomain which binds VEGF and PlGF and can antagonize the effects of VEGF in the extracellular milieu. To further evaluate Flt1 processing we expressed tagged Flt1 constructs in HEK293 and COS7 cells where we demonstrate, by deletion mapping, that the cleavage site is immediately adjacent to the transmembrane domain (TMD) between residues 759 and 763. Cleavage reciprocally regulates free VEGF in conditioned media and we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…We have previously reported that the single-pass membrane receptor FLT1 is cleaved twice: one cleavage occurs in the extracellular region to shed an NH 2 -terminal fragment (NTF; cFLT1) into the extracellular milieu, leaving a membranetethered COOH-terminal fragment (CTF1), and another cleavage occurs independently within or just after the transmembrane domain to release a cytosolic COOH-terminal fragment, CTF2 (21). Extracellular cleavage is mediated by ADAM10 and ADAM17 and stimulated by protein kinase C (PKC), and the cleaved fragment of FLT1 (cFLT1) binds VEGF-A and PlGF with high affinity and thus functions as a soluble PlGF/ VEGF antagonist regulating angiogenesis in vitro (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that the single-pass membrane receptor FLT1 is cleaved twice: one cleavage occurs in the extracellular region to shed an NH 2 -terminal fragment (NTF; cFLT1) into the extracellular milieu, leaving a membranetethered COOH-terminal fragment (CTF1), and another cleavage occurs independently within or just after the transmembrane domain to release a cytosolic COOH-terminal fragment, CTF2 (21). Extracellular cleavage is mediated by ADAM10 and ADAM17 and stimulated by protein kinase C (PKC), and the cleaved fragment of FLT1 (cFLT1) binds VEGF-A and PlGF with high affinity and thus functions as a soluble PlGF/ VEGF antagonist regulating angiogenesis in vitro (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Expression vectors. Expression vector carrying cDNA for HA-FLT1-Myc-Flag, FLT1⌬CTD, FLT1⌬729 -758, and FLT1Y1333F have been described before (21)(22)(23). COOH-terminal turbo-GFPtagged open reading frame clone of full-length human VEGFR2 (KDR) was purchased from OriGene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations